Development of Sex Education Model as An Extracurricular Activity in High School to Improve Understanding and Attitude of Care for Reproductive Health - Evira Yustika; Wiwi Isnaeni; Dyah Rini Indriyanti; Aditya Marianti (Universitas Negeri Semarang, 2023)
The problem of free sex among adolescents is increasing from year to year, this is because teenagers do not understand and care less about the health of the reproductive organs. The research aims to increase understanding and caring attitude towards the health of the reproductive organs. The development of the sex education model is carried out using the ADDIE development model through 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. Teaching materials use the Flipbuilder application, the use of the application is expected to make it easier for students to learn. This research also developed other learning tools in the form of lesson plans, syllabi, and other learning assessments. the results of device development obtained reproductive system teaching materials that are valid and suitable for use. The results of the questionnaire from material experts reached 89% (very high), while the validation of teaching materials experts reached 90.48% (very high). At the implementation stage, the effectiveness of the sex education model with teaching materials using the flip-builder application was obtained based on an understanding of 87 (very good). The attitude of students towards caring for the health of the reproductive organs is 65% (good). Students' responses during the biology learning process in class using the sex education model and flip-builder application teaching materials said the students were good to be implemented in class